If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5a + 4 + 6a = 10 + -19 Reorder the terms: 4 + -5a + 6a = 10 + -19 Combine like terms: -5a + 6a = 1a 4 + 1a = 10 + -19 Combine like terms: 10 + -19 = -9 4 + 1a = -9 Solving 4 + 1a = -9 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 1a = -9 + -4 Combine like terms: 4 + -4 = 0 0 + 1a = -9 + -4 1a = -9 + -4 Combine like terms: -9 + -4 = -13 1a = -13 Divide each side by '1'. a = -13 Simplifying a = -13
| -3(2x+1)+20=8x+5 | | 384-6x^2=0 | | 5=20a | | 7x-3x+9=29 | | -6x+17=8x+5 | | 5x-19=-7 | | 109-x=167 | | 3+5z= | | 6n-2=-68 | | -2.4k=42 | | b+5-6=18 | | 95+x=x | | 2x=-21+3 | | -0.54=.36m | | 195/200 | | 5+90=x | | 3x-30/18 | | -4-9=13-5x | | 24=4v | | -2/3(8x-9) | | -6(2s+6)= | | 20logx=-50 | | 6x+3-6x= | | (3x-10)=x | | -3y^2-3x=0 | | 30+x+60=180 | | 2x-86=7x+59 | | -3.2/5 | | X+60=x | | 3x^2-2y^2=48 | | 25+2T= | | 18(x-3)=180 |